The Professionalism in Collaboration between Health and Social Care Workers: A Survey to Members of the Finnish Trade Unions - Pakkanen, Piiku; Haeggman-Laitila, Arja; Pasanen, Miko; Kangasniemi, Mari (WILEY, 2025)
Background. Professionalism in collaboration means working based on competencies and ethics, showing accountability and respect in communication and care by each professional group. It is required to ensure seamless, integrated, and quality of care for patients. Previous research has focused on professionalism among single professional groups; little is known about how ethics of professionalism appear in collaboration between different professional groups. Our aim was to fill the gap in this knowledge. The objectives of the study were how health and social care workers evaluated professionalism in collaboration, how professionalism was associated with the various professional groups, and how it was related to the personal characteristics of the workers.
Methods. A cross-sectional study with an online survey was conducted in collaboration with 15 professional trade unions in Finland. The 26-item Interprofessional Professionalism Assessment questionnaire was used. The R program, version 4.0.2, was used for advanced descriptive and statistical methods.
Results. Together, 1,769 trade union members participated in the study, representing eight professional groups and students from care, rehabilitation, and social services. The mean professionalism score was 4.20 +/- 0.70 out of 5, suggesting excellent professionalism in collaboration. Care assistants, childcare and youth workers, and nurses scored professionalism statistically significantly higher than social workers (p<0.001). Participants who experienced mutual ethical reflections at work (p<0.001), received organizational support for ethical practice (p<0.01), and experienced satisfaction at work (p<0.001) scored professionalism statistically significantly higher.
Conclusions. Professionalism in collaboration between health and social workers was very consistent and strong, despite the fact that different professional groups participated in the survey. Organizations should further work satisfaction and opportunities to participate in shared ethical reflection. Future studies should investigate organizational structures and leadership that support this kind of well-executed professionalism in collaboration between professional groups and if workers recognize these.